2010
DOI: 10.1100/tsw.2010.188
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Vitamin A Capsule Supplementation Coverage in Nigeria: A Multilevel Analysis of Geographic and Socioeconomic Inequities

Abstract: Vitamin A deficiency (VAD) is a huge public health burden among preschool-aged children in sub-Saharan Africa, and is associated with a high level of susceptibility to infectious diseases and pediatric blindness. We examined the Nigerian national vitamin A capsule (VAC) supplementation program, a short-term cost-effective intervention for prevention of VAD-associated morbidity for equity in terms of socioeconomic and geographic coverage. Using the most current, nationally representative data from the 2008 Nige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
18
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 51 publications
8
18
1
Order By: Relevance
“…This finding is consistent with the findings of previous studies conducted by Lerebo (2010), which disclosed that; in comparison to children whose region of residence was Affar region, children from Addis Ababa and Dire Dawa City, Tigray, Harari, Amahara, Gambella, SNNP, Oromia, Somalia and BEGU regions had higher chance of being fully immunized [ 26 ]. Similarly, different studies conducted elsewhere had found the significant effect of regional variations on childhood full immunization status [ 14 , 23 , 31 – 33 ]. This may be due to the fact that the 9 regional states and 2 city administrative councils found in Ethiopia consists of different religious, cultural, population size, geographic nature and levels of development.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This finding is consistent with the findings of previous studies conducted by Lerebo (2010), which disclosed that; in comparison to children whose region of residence was Affar region, children from Addis Ababa and Dire Dawa City, Tigray, Harari, Amahara, Gambella, SNNP, Oromia, Somalia and BEGU regions had higher chance of being fully immunized [ 26 ]. Similarly, different studies conducted elsewhere had found the significant effect of regional variations on childhood full immunization status [ 14 , 23 , 31 – 33 ]. This may be due to the fact that the 9 regional states and 2 city administrative councils found in Ethiopia consists of different religious, cultural, population size, geographic nature and levels of development.…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies had identified factors associated with childhood full immunization which include, child place of delivery [ 14 – 18 ], age of child [ 17 , 19 , 20 ], birth order of the child [ 15 , 18 , 21 , 23 – 25 ], number of under 5 years children in the household [ 22 ], maternal age [ 14 , 19 , 20 ], parental education [ 7 , 18 – 20 , 22 , 23 , 25 – 27 ], family wealth index [ 13 – 15 , 23 , 25 , 28 ], parental employment status [ 19 , 29 ], maternal marital status [ 15 , 17 , 19 , 25 ], antenatal care (ANC) and tetanus toxoid (TT) [ 17 ], religious affiliation [ 14 , 26 , 28 ], and exposure to mass media [ 13 ] and at the community level place of residence [ 7 , 17 , 19 , 20 , 23 , 26 , 29 , 30 ], geographic region [ 21 , 23 , 26 , 31 – 33 ], community maternal hospital delivery [ 21 , 31 ], community/neighborhood poverty [ 33 ], community maternal unemployment and illiteracy [ 19 ], distance from health facility [ 31 ] and community maternal ANC services utilization were found to be associated with immunization status.…”
Section: Introductionmentioning
confidence: 99%
“…Second, use of an asset based index as a surrogate measure of household wealth may be criticized. However, the use of an asset based index as a proxy for household wealth has been shown to be reliable 30,45. These limitations notwithstanding, the strength of this study is in the novelty of its findings, which provide a new insight into the existing body of evidence in the research area examined.…”
Section: Study Limitations and Strengthsmentioning
confidence: 87%
“…According to the Ethiopian DHS 2016, percentage given VAS in the past 6 months increased from 41% among children from the poorest households to 58% to those from richest households [5]. Aremu et al in Nigeria also identi ed household wealth status as the only household-level characteristic that signi cantly affect receipt of vitamin A capsule [27]. Better household wealth standing may improve uptake of the supplement through advancing access to health information and mitigating economic barters for seeking health care.…”
Section: Discussionmentioning
confidence: 99%